Bio-template synthesis of hollow Fe3O4 fibers and their enhanced microwave absorption performance in Ku-band. Issue 172 (12th June 2016) - Liu, Qiangchun; Huang, Fei; Zi, Zhenfa; Zhang, Min; Dai, Jianming
ABSTRACT: A novel kind of microwave absorption composite in Ku-band with low cost, low density and strong absorption was prepared through Bio-template carbonization and solvothermal method. The phase structures and morphologies of the composite had been characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The microwave absorption properties of carbonized kapok fibers and Fe3 O4 /kapok fibers were measured by vector network analysis (VNA). When the sample thickness is 1.5 mm, the Fe3 O4 /kapok fibers have an optimal absorption peak value of about −24.1 dB at 17.4 GHz and its effective absorption bandwidth lower than −10 dB reaches 2.4 GHz (from 15.6 to 18.0 GHz). The reflection loss results indicate that the Fe3 O4 /kapok fibers possess higher microwave absorption in the Ku-band. A possible mechanism of the improved microwave absorption performance of the composite was discussed.